Ford v Ferrari [videorecording (DVD)] - Mangold, James; Mangold, James; Damon, Matt; Bale, Christian, 1974-; Bernthal, Jon (Twentieth Century Fox Home Entertainment, 2020)
Follows automobile designer Carroll Shelby and driver Ken Miles as they lead a team for Ford to build a race car that can defeat Ferrari at the 24 Hours of Le Mans race in 1966.